Parent support contribution and peer conformity on learning motivation - Anggi Fadilah; Marjohan Marjohan (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
One that affects the success of student learning is motivation. Less motivation to learn in students will affect the decrease in enthusiasm for learning and learning outcomes. There are several factors that influence the motivation of students in learning, including the support of parents and peers. This research aims to; (1) Describe the contribution of parental support, peer conformity and students' learning motivation, and (2) examine the contribution of parental support and peer conformity together on students' learning motivation. This study uses a quantitative approach with analytical descriptive method. The sample in this study were students of class VII and VIII, a total of 108 students. This research instrument uses a Likert scale model. The data were analyzed by descriptive statistical techniques, then using simple linear regression analysis and multiple linear regression analysis. The research findings show that in general; 1) students' parental support is in the high category, peer conformity of students is in the very high category, students' learning motivation is in the very high category, and 2) there is a strong and positive relationship between parental support and students' learning motivation. . This research has implications for the educational process in schools as a contribution to parental support and positive peer conformity which makes students have high learning motivation and are confident in their own abilities.